Alishewanella solinquinati sp nov., isolated from soil contaminated with textile dyes - Kolekar, Yogesh M.; Pawar, Shrikant P.; Adav, Sunil S.; Zheng, Liu-Qiang; Li, Wen-Jun; Shouche, Yogesh S.; Dastager, Syed Gulam; Kodam, Kisan M. (Current Microbiology, 2013)
A novel Gram-negative, motile, rod-shaped, facultative anaerobic bacterial strain, KMK6(T), was isolated from soil contaminated with textile dyes from an industrial estate located at Ichalkaranji, Maharashtra, India, and its taxonomical position was established by using a polyphasic approach. The major cellular fatty acids included C-17:1 omega 8c, summed feature 3 (C-16:1 omega 7c and/or iso-C-15:0 2-OH), C-17:0, C-16:0,C- and C-18:1 omega 7c. The DNA G+C content of strain KMK6(T) was 48.8 mol %. 16S rRNA gene sequence analysis confirmed its placement in the genus Alishewanella, and exhibited sequence similarity levels of below 97 % to the type strains of validly published Alishewanella species. On the basis of genotypic and phenotypic evidence, strains KMK6(T) is considered to be a novel species of the genus Alishewanella, for which we propose that strain KMK6(T) (=NCIM 5295(T) =BCRC 17848(T)) is assigned to a novel species, Alishewanella solinquinati sp. nov.